Teaching elementary students real-life inquiry skills - Hill, Kristy (Libraries Unlimited, 2019)
This book shows how to teach elementary students to locate reliable information, evaluate sources, develop their writing skills in the classroom and in the library, evaluate information, and collect it from credible sources. It explains how to incorporate writing into your makerspace, encourage curiosity through the inquiry process, help students find their voice, and support writing and prewriting for digital media. Includes lesson plans, student samples, and activities.
Keywords: Research -- Methodology -- Study and teaching (Elementary); Information literacy -- Study and teaching (Elementary); School librarian participation in curriculum planning.; Inquiry-based learning.; Lesson planning.; Makerspaces in libraries.; Writing centers.; Recherche -- Méthodologie -- Étude et enseignement (Primaire); Culture de l'information -- Étude et enseignement (Primaire); Bibliothécaires scolaires -- Participation à la planification des programmes d'études.; Apprentissage basé sur l'enquête.; Préparation de cours.; Laboratoires ouverts dans les bibliothèques.; Centres de communication écrite.; Library & information sciences.; Inquiry-based learning; Lesson planning; Makerspaces in libraries; School librarian participation in curriculum planning; Writing centers